Resistência cruzada de junquinho aos herbicidas inibidores da ALS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Cyperus iria (CYPIR) is one of the main weeds in irrigated rice crops. The intense chemical control with acetolactate synthase (ALS) inhibiting herbicides favors the selection of cross-resistance. This study aimed at evaluatinge the cross-resistance of CYPIR to ALS-inhibiting herbicides in irrigated rice in Rio Grande do Sul. Two experiments arranged in a factorial scheme, in a completely randomized design, with four replications were conducted. Experiment I consisted of resistant (CYPIR-R) and susceptible (CYPIR-S) biotypes and ALS-inhibiting herbicide doses: imazethapyr (106 g a.i. ha-¹); pyrazosulfuron-ethyl (20 g a.i. ha-¹); penoxsulam (36 g a.i. ha-¹) and, as an alternative herbicide, bentazone (960 g a.i. ha-¹); corresponding to 0; 1/16; 1/8; 1/4; 1/2; 1; 2; 4; 8 and 16x (x = maximum registered dose). Experiment II followed the same procedures, with doses of 0; 1/64; 1/32; 1/16; 1/8; 1/4; 1/2; 1 and 2x for CYPIR-S and 0; 1/2; 1; 2; 4; 8; 16; 32; 64 and 128x for CYPIR-R; including bispyribac-sodium (x = 50 g a.i. ha-¹). The variables evaluated were: visual control at 7, 14, 21 and 28 days after the treatments (DAT) and shoot dry matter (SDM) at 28 DAT. The results, fitted by nonlinear regression, show varied and high levels of cross-resistance of CYPIR-R to ALS-inhibiting herbicides from the group of imidazolinones, sulfonylureas, triazolopyrimidines and pyrimidinyl(thio)benzoates. Bentazone can be used as an alternative herbicide, however, not exclusively in the control of this biotype.
Keywords: Oryza sativa; Cyperus iria (CYPIR); Curva de dose-resposta; Biótipo resistente; Dose-response curve; Resistant biotype; CNPQ::CIENCIAS AGRARIAS